2014
DOI: 10.1021/nn406484b
|View full text |Cite
|
Sign up to set email alerts
|

Lung Macrophages “Digest” Carbon Nanotubes Using a Superoxide/Peroxynitrite Oxidative Pathway

Abstract: In contrast to short-lived neutrophils, macrophages display persistent presence in the lung of animals after pulmonary exposure to carbon nanotubes. While effective in the clearance of bacterial pathogens and injured host cells, the ability of macrophages to “digest” carbonaceous nanoparticles has not been documented. Here, we used chemical, biochemical, and cell and animal models and demonstrated oxidative biodegradation of oxidatively functionalized single-walled carbon nanotubes via superoxide/NO* → peroxyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 51 publications
5
127
0
Order By: Relevance
“…The reaction rate constant between O 2 ·− and NO is as high as 6.7 × 10 9 L mol −1 s −1 , which is about 30 times of that between O 2 ·− and luminol radical (2.3 × 10 8 L mol −1 s −1 ) [32,33]. Moreover, the produced ONOO − is a much stronger oxidant (with a redox potential of 1.4 V) than O 2 ·− [34,35] and can first react with luminol to produce an unstable endoperoxide intermediate, which decays to ground state aminophthalate with emission of light [36]. Thus, CL signal in the reaction system is mainly emitted from endoperoxide intermediate oxidized by ONOO − .…”
Section: Resultsmentioning
confidence: 94%
“…The reaction rate constant between O 2 ·− and NO is as high as 6.7 × 10 9 L mol −1 s −1 , which is about 30 times of that between O 2 ·− and luminol radical (2.3 × 10 8 L mol −1 s −1 ) [32,33]. Moreover, the produced ONOO − is a much stronger oxidant (with a redox potential of 1.4 V) than O 2 ·− [34,35] and can first react with luminol to produce an unstable endoperoxide intermediate, which decays to ground state aminophthalate with emission of light [36]. Thus, CL signal in the reaction system is mainly emitted from endoperoxide intermediate oxidized by ONOO − .…”
Section: Resultsmentioning
confidence: 94%
“…Recent evidence has also reported the possibility of the degradation of CNTs by cells, such as neutrophils, 32 microglia, 33 and macrophages. [34][35][36] Overall, the current data suggest that the toxicity of MWCNTs can be at least partly reduced or minimized by improving design strategies of short-length MWCNT with appropriate surface modifications that are feasible for degradation by cells after the delivery of loaded proteins or drugs.…”
mentioning
confidence: 89%
“…The outer and inner Fe@MWCNT diameters (ODs and IDs) were nonuniform and varied not only between different but also for particular nanotubes; ODs and IDs were found to be equal to 44 ± 25 and 12 ± 6 nm, respectively. The length of pristine nanotubes was 100±20 m, while oxidation led to their partial cutting and the length was reduced to 50±30 m yielding nanotubes which fall into a biocompatible and water-dispersible category [19][20][21]. Raman spectrum of Fe@MWCNT (Figure 1(c)) shows three dominating signals at 1332, 1579, and 2662 cm −1 which can be assigned to D-(disorder), G-(tangential graphite), and G -(second-order harmonic) bands, respectively [45].…”
Section: Synthesis and Physicochemical Properties Of Nanotubementioning
confidence: 99%
“…On the other hand, today, there is no doubt that short, functionalized with polar moieties, and individualized MWCNTs offer a hope to be tested clinically [16]. But earlier in vitro [17] and in vivo [18] reports confirmed that, after functionalization, even >40 m long Fe@MWCNTs, providing individualized (i.e., not aggregated) nanotubes, could be considered as enzymatically degradable [19,20] and hence excretable drug vehicles [21].…”
Section: Introductionmentioning
confidence: 99%